Neuroendocrine characterization into schizophrenia: norepinephrine and melatonin as promising biomarkers - Shen, Junwei; Li, Xin; Zhong, Yinghua; Zhang, Jiechun; Qin, Hongyun; Chen, Fazhan; Zhao, Xudong (Frontiers in Endocrinology, 2025)
BackgroundAlthough brain-derived neurotrophic factor (BDNF)has garnered extensive attention as a neuroendocrine marker in schizophrenia (SZ), its clinical utility remains limite due to inconsistent findings.MethodsTo address this gap, serum samples were collected from 24 female patients with SZ and 25 healthy controls. The metabolic profiling was performed using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS) to capture abroad range of metabolites.ResultsOur results revealed that BDNF is not a robust discriminatory biomarker. Marked differences in metabolic profiles were identified between patients with SZ and healthy individuals. The GC-MS analysis revealed significant differences in 79 metabolites; while the LC-MS analysis identified 419 significantly differential metabolites. Functional analysis reveals that these differential metabolites predominantly contribute to metabolic and neuro-related processes. Our findings demonstrate that norepinephrine and melatonin, two additional neuroendocrine compounds, are significantly elevated in patients with SZ compared to healthy controls. Notably, their higher areas under the curve (AUC) values compared to BDNF highlight their potential as more reliable biomarkers for SZ.ConclusionThis study offers valuable insights into the altered metabolic patterns of female patients with SZ and establishes melatonin and norepinephrine as promising neuroendocrine biomarkers, underscoring their diagnostic value and role in the neuroendocrine regulation of mental disorders.